Interview mit Georgina Beier und Katharina Greven (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2015)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Interviews; Women artists; Artists; Nigeria; Papua New Guinea; New Guinea; Art Collector; Art Collecting